2001
DOI: 10.1159/000051275
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and Cognitive Decline in Healthy Elderly

Abstract: Serum homocysteine is increased, and correlates inversely with cognitive scores, in Alzheimer’s disease (AD), vascular dementia and ‘age-associated memory impairment’. Elevated levels might signal accelerated cognitive decline, although this remains to be established. We therefore repeated Mini-Mental State Examinations, together with additional ADAS-Cog assessments, in 32 healthy elderly individuals to determine whether prior homocysteine levels predicted cognitive changes over a 5-year period. Homocysteine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
2
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(139 citation statements)
references
References 16 publications
7
127
2
3
Order By: Relevance
“…There are three main public health concerns with regard to increased plasma homocysteine levels: increased risk of cardiovascular diseases (Clarke et al, 1991;Boushey et al, 1995;Ueland et al, 2000), reproductive hazards (Wouters et al, 1993;Goddijn-Wessel et al, 1996;Leeda et al, 1998;Sorensen et al, 1999;Nelen et al, 2000;Vollset et al, 2000a, b;Refsum, 2001) and the possible association to cognitive disorders (Clarke et al, 1998;McCaddon et al, 2001;Seshadri et al, 2002). The effect of increased plasma homocysteine levels on certain reproductive hazards is currently accepted as causal, whereas the effect on coronary heart disease is still under investigation and awaits the results of intervention studies (Ubbink & Delport, 2000;Ueland et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…There are three main public health concerns with regard to increased plasma homocysteine levels: increased risk of cardiovascular diseases (Clarke et al, 1991;Boushey et al, 1995;Ueland et al, 2000), reproductive hazards (Wouters et al, 1993;Goddijn-Wessel et al, 1996;Leeda et al, 1998;Sorensen et al, 1999;Nelen et al, 2000;Vollset et al, 2000a, b;Refsum, 2001) and the possible association to cognitive disorders (Clarke et al, 1998;McCaddon et al, 2001;Seshadri et al, 2002). The effect of increased plasma homocysteine levels on certain reproductive hazards is currently accepted as causal, whereas the effect on coronary heart disease is still under investigation and awaits the results of intervention studies (Ubbink & Delport, 2000;Ueland et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The association between tHcy and Alzheimer disease is dose dependent and even stronger in those with histopathologically confirmed diagnosis (192 ). Increased tHcy or low folate or cobalamin precedes cognitive decline (194 -196 ): Hyperhomocysteinemic individuals have an increased rate of atrophy of the medial temporal lobe (192 ) and a more rapid decrease in cognitive test scores (194 ). A large prospective study showed that increased tHcy up to 11 years before the diagnosis of dementia is associated with twice the risk of Alzheimer disease (196 ).…”
Section: Psychiatric Disorders and Cognitive Impairmentmentioning
confidence: 99%
“…Some have shown significant associations between homocysteine levels and cognitive function, 10,[12][13][14][15][16][17][19][20][21][22] whereas others have not. 11,18 An early study involving a small sample of a healthy elderly population in Italy showed no significant correlations between the Mini-Mental State Exam (MMSE) scores and homocysteine levels.…”
Section: Homocysteine and Cognitive Function Scoresmentioning
confidence: 99%